THE VALIDITY OF CRIMINAL OFFENDER ARREST IN THE IMMIGRATION AREA AS A REASON FOR EXIT BAN TO LEAVING THE TERRITORITY OF INDONESIA -CASE STUDIES OF RATNA SARUMPAET - M. Alvi Syahrin; Rio Restu Prabekti (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Arrest is an act of the investigator to temporarily restrict the freedom of the suspect or accused if there is sufficient evidence for proposes of investigation or prosecution and/or adjudication in matters and by means regulated in the law. One of the cases that has caught the public's attention is the prevention and arrest of Ratna Sarumpaet who is a suspect in the case of spreading hoaxes in the immigration area of Soekarno-Hatta International Airport. This research has the formulation of the problem whether the prevention of going abroad and the arrest of suspect Ratna Sarumpaet in the immigration area is in accordance with applicable regulations. The purpose of this study is to determine whether the forced efforts made in this case the arrest and prevention of Ratna Sarumpaet violates the rules or not. This research is a normative study using several problem approaches which include the Law approach and analysis approach. The data sources used are secondary data, namely library materials which include library books, legislation, and others. Data will be analyzed by normative analysis method. The theoretical basis used is the rule of law theory, the theory of state sovereignty, the theory of law enforcement and the theory of criminal law. Based on the data analysis, it was concluded that the prevention of leaving the Territory of Indonesia and the arrest of Ratna Sarumpaet which was a forced attempt by the police in coordination with the immigration party were in accordance with applicable regulations, namely as stipulated in the Criminal Procedure Code, Law Number 6 2011 concerning Immigration and Government Regulation Number 31 of 2013 concerning Regulations for the Implementation of Law Number 6 of 2011 concerning Immigration.